Community Participation at the Basic Education Level in Wakatobi Regency - Edy Karno; Syahrul Syahrul (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This article aims to provide an overview of community participation in education in Wakatobi District. The aspects explored include: pure enrollment rates at primary education level, literacy rates of people aged 15 years and over, and average length of schooling of residents aged 15 years and over. This study uses a qualitative approach, in which document study becomes the main technique in data collection. The document examined is the archive of the Education and Culture Office, as well as the Wakatobi Regency Central Statistics Agency. Data analysis is carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results showed that: 1) Elementary School Participation Rate (APS) was more than 95 percent and APSSMP was more than 76.15 percent. This shows that the 6-year Compulsory Education supported by school infrastructure development and continued with the 9-year Compulsory Education is an education sector program that is recognized as quite successful. In other words, compulsory learning programs are said to be successful. 2) Literacy rates are seen in the proportion of diploma ownership by sex. Where elementary school level is equal and diploma and above, the proportion of women with a diploma tends to be higher than the male population. While at the level of junior high school and senior high school, the proportion of the male population with a diploma tends to be higher than the female population. 3) during the 2010-2016 period, the average length of schooling in Wakatobi District had increased from 2010 by 6.18 years, in 2016 to 7.70 years.